Influence of soil stiffness and lateral stress on the results of in-situ soil tests - Houlsby, G; Wroth, C (Publ by A.A. Balkema, 1989)
The results of in-situ tests depend on the strength, stiffness and permeability properties of the ground, as well as the in-situ stresses. Laboratory and theoretical studies have shown that two quantities are particularly important in the understanding of in-situ tests: the horizontal stress and the soil stiffness. The effect of these quantities on test results can sometimes be advantageous, in that it can allow the stiffness or horizontal stress to be estimated, but is more often inconvenient, since it adds a degree of uncertainty to the interpretation of the tests. Results are presented for the cone penetrometer, piezocone, Marchetti dilatometer and cone-pressuremeter, and tests in both clays and sands are considered. Recommendations are made for use of appropriate in-situ tests in different circumstances.